FIXED-TERM EMPLOYMENT CONTRACT AND ITS ABUSES - Radovanović, Jelena (Glasnik Advokatske komore Vojvodine, 2025)
A fixed-term employment contract is a flexible form of employment that allows employers to respond to the temporary needs of the labor market. However, in practice this form of employment is often abused, which leads to employee insecurity and violation of labor rights. This paper analyzes the legal framework and purpose of fixed-term employment contracts and identifies the most common forms of abuse. In conclusion, recommendations are proposed for improving legislation and strengthening supervision over the implementation of fixed-term employment contracts in order to reduce abuses and improve the protection of workers' rights. The hypothesis is based on that the positive legal provisions have not clearly determined the situations in which a fixed-term employment relationship can be established, but it is necessary to determine precise and concrete circumstances that are characteristic of a certain activity and that can only exceptionally justify the absence of the need for a permanent employment of the employee, as well that insufficient capacities of labor inspection and other mechanisms to prevent abuse of fixed-term employment contract, facilitate the violation of regulations in this area of ​​labor law in the Republic of Serbia, by employers, as the stronger party in the employment relationship.
Keywords: employment relationship; fixed-term employment contract; abuse; violation of labor rights